INTERNATIONAL APPROACHES TO CORRECTING LEXICAL-GRAMMATICAL MISTAKES IN LEARNERS’ WRITING - Muminova Dilnora Nuriddinovna (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
Abstract: This article examines the most influential international approaches to correcting lexical-grammatical mistakes in learners’ writing. It analyzes traditional, cognitive, communicative, sociocultural, and technology-enhanced methods used in foreign language teaching around the world. The study compares direct and indirect feedback strategies, explores teacher, peer, and self-correction techniques, and evaluates the effectiveness of automated digital tools. The paper concludes with recommendations for adopting an integrated, learner-centered correction model suitable for diverse educational contexts.